Student Learning Interest in Following Health and Sports Physical Education in Madrasa Studentsaliyah Al-Falah Debowae Kabupaten Buru - Ratna Sari; B. Hasbullah; Emma Rumahlewang (Peneliti.net, 2023)
The aim of this study was to determine the learning interest of Madrasa Aliyah Al-Falah Debowae Debowae students in Buru Regency in the subjects of physical education, sport and health. The specific objectives of this study were to find out: Students' interest in PJOK subjects at Madarasah Aliyah Al-Falah Debowae Buru District. This research is a quantitative study using a survey approach, while the variable studied is interest in learning sports physical education at MA al- falah Debowae, Buru district. By using a questionnaire or questionnaire as a data collection tool, in addition to that, this study attempted to describe and generalize data or events that occurred to all members of the population based on the research sample. From the results of the research and discussion that have been described, it can be concluded that: a. That the interest of students in participating in physical education, sports and health lessons at MA Al-Falah Debowae, Buru Regency, is in the medium category with 27 students or 45%. b. In students' interest in learning Physical Education, Sports and Health, there are 5 indicators, namely attention, feelings of pleasure, activity, the role of the teacher and facilities. With the results of each indicator, namely: attention indicators have the most categories, namely moderate (28 students) with a percentage of 46.7%, indicators of feeling happy have the most categories, namely moderate (19 students) with a percentage of 31.6%, activity indicators have categories the most is moderate, (34 students) with a percentage of 56.7%, the teacher's role indicator has the most category, namely medium (26 students) with a percentage of 43.4% and the category of facilities has the most category, namely high (29 students) with a percentage of 48.3 %. 1. Schools must be able to foster student interest in learning by increasing the factors that influence student learning interest. 2. The research instrument is less broad in scope so that it is possible that there are more important elements that are not included / not disclosed in the research instrument. because of that there is an instrument to add so that this research is even better. 3. With these results it can be used as a reference for schools and teachers to control student learning interest as a supporter of successful learning